Cytomegalovirus remains viable in naturally infected breast milk despite being frozen for 10 days. Issue 6 (21st October 2005) - Curtis, N; Chau, L; Garland, S; Tabrizi, S; Alexander, R; Morley, C J
Abstract : Cytomegalovirus culture positive breast milk was obtained from four mothers of very premature babies. The milk was stored at 0–5°C in a domestic refrigerator for 48 hours or frozen for different durations at −20°C. Cytomegalovirus survived in breast milk despite being frozen for 10 days at −20°C.